One Decade of Inquiry-Based Learning in Education: Trends and Hot Topics - Fadillah, Muhammad Aizri; Usmeldi, Usmeldi; Lufri, Lufri; Mawardi, Mawardi; Festiyed, Festiyed (Peneliti.net, 2024)
The popularity of Inquiry-Based Learning (IBL) has continued to increase in the last decade, as reflected in the growing number of academic publications examining its implementation and impact across various disciplines. This study aims to analyze publication trends and hot topics related to IBL over the past decade using a bibliometric approach. A total of 236 Scopus-indexed documents were analyzed. The analysis showed a significant increase in the number of IBL publications and citations. Indonesia dominates the research contributions, indicating successful educational reforms that support the adoption of IBL. Physics and Astronomy were the disciplines that adopted this approach the most, followed by Social Sciences. Keyword analysis identified four main themes that were being discussed: attitude, character, cognitive style, and metacognition. The findings show the importance of a holistic approach to IBL learning, which includes both cognitive and non-cognitive dimensions. This study concludes that IBL is an effective pedagogical approach that continues to evolve. Further research is recommended to explore the integration of these key themes within a more inclusive IBL framework, as well as cross-cultural applications, to support more relevant and meaningful learning.